2018
DOI: 10.17505/jpor.2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting measurement invariance in intelligence testing in aging research: Evidence for almost complete metric invariance across age groups

Abstract: Almost complete metric invariance holds for a two-factor model of intelligence. Most of the subtests were invariant across age groups, suggesting little evidence for age-related bias in the WAIS-R. However, we did find unique relationships between two subtests and intelligence. Future studies should examine age-related differences in subtests when testing measurement invariance in intelligence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Sprague et al’s (2017, p. 86) observation that “invariance of intelligence across age is often assumed but infrequently explicitly tested” also applies to gc. Thus, the current results are important for age-comparative research, where gc is to be compared across individuals of differing age.…”
Section: Discussionmentioning
confidence: 99%
“…Sprague et al’s (2017, p. 86) observation that “invariance of intelligence across age is often assumed but infrequently explicitly tested” also applies to gc. Thus, the current results are important for age-comparative research, where gc is to be compared across individuals of differing age.…”
Section: Discussionmentioning
confidence: 99%
“…investigated 940 participants aged 16–75 and found that performance in BDT decreases with increasing age. [ 9 ] Another study reported a strong decline in the BDT performance with aging, although variability also significantly increases in older age groups. [ 7 ] One study suggests that visuospatial ability is preserved in older people, and poorer performance is caused by slower visuomotor speed.…”
Section: Discussionmentioning
confidence: 99%
“…This test has been used in other research assessing visuospatial function of older people. [ 7 8 9 10 ]…”
Section: S Ubjects and M Ethodsmentioning
confidence: 99%
“…In singlesession studies, the method variance is confounded with true variance at the subject's level of analysis. Longitudinal studies could estimate the variance of the latent dimensions separately between the subjects (inter-subject level of analysis, between) and the temporal effect (intra-subject level, within), and could also test if the same variation of the specific and general dimensions is observed at both levels (Pornprasertmanit et al 2014;Richerson et al 2014;Sprague et al 2017). In other words, it could be assessed whether the shared general variance has a similar structure between the levels of analysis, which would reduce the chances of a general spurious dimension.…”
Section: Discussionmentioning
confidence: 99%